Error Correction Model Approach for Problematic Financing Analysis at BPRS Lantabur Tebuireng for the 2020-2024 Period - Yusron Fikri Nurwakhid; Ika Septiana Windi Antari (Institut Agama Islam Negeri Ponorogo, 2025)
Introduction: This study is a quantitative study that aims to determine the effect of BOPO, CR and CAR on Non-Performing Financing (NPF). The analysis technique used in this study is the Error Correction Model (ECM) with a significance level of 5%. Research Methods: This data collection method is in the form of secondary data, namely the quarterly financial report data of BPRS Lantabur Tebuireng for the 2020-2024 period from the NPF variable obtained from the official OJK website. Results: The results of this study indicate that BOPO in the short term has no effect on NPF, while in the long term it has an effect on NPF. CR in the short term has no effect on NPF, while in the long term, it has an effect on NPF. CAR in the short term and long term has no effect on NPF. Conclusion: BOPO, FDR, and CAR simultaneously in the short term have no significant effect on NPF, while in the long term, they have a significant effect on NPF.